An unusual cause of abdominal distension: intraperitoneal bladder perforation secondary to intermittent self-catheterisation. (25th February 2015) - Martin, Jennifer; Convie, Liam; Mark, David; McClure, Mark
Abstract : We report a strikingly unusual case of traumatic intraperitoneal perforation of an augmented bladder from clean intermittent self-catheterisation (CISC), which presented a unique diagnostic challenge. This case describes a 48-year-old T1 level paraplegic, who had undergone clamshell ileocystoplasty for detrusor overactivity, presenting with abdominal distension, vomiting and diarrhoea. Initial investigations were suggestive of disseminated peritoneal malignancy with ascitic fluid collections, but the ascitic fluid was found to be intraperitoneal urine from a perforation of the urinary bladder. This was associated with an inflammatory response in the surrounding structures causing an appearance of colonic thickening and omental disease. Although the diagnostic process was complex due to this patient's medical history, the treatment plan initiated was non-operative, with insertion of an indwelling urinary catheter and radiologically guided drainage of pelvic and abdominal collections. Overdistension perforations of augmented urinary bladders have been reported, but few have described perforation from CISC.